Gender Differences in Common Mental Disorders - Nashi Khan, Amira Amjad, Anum Farooq , Rukhsana Kausar (Pakistan Journal of Clinical Psychology, 2016)
Objective: This study aims to examine gender differences in common mental disorders in Pakistan Design: Survey Research Design was used in the present study. Sample: 219 married and unmarried men (n=35) and women (n= 184) experiencing mild and transitory medical conditions. Place and Duration of Study: The sample was recruited from General Practitioners’ clinics located in dense areas and free dispensaries in Lahore. Method: Symptom Checklist-R (Rahman, Dawood, Rehman, Mansoor, & Ali, 2009) and General Health Questionnaire (GHQ-28) Urdu Version (Minhas & Mubbashar, 1996) were administered on the participants to identify common mental disorders. Results: Results revealed the presence of significant gender differences with women scoring significantly higher on Depression, Somatization, Anxiety and Low Frustration Tolerance. Data revealed that a huge majority (91% women and 80% men) were experiencing Psychological Distress. This signified that though women tend to experience more Common Mental Disorder than men however both of them were experiencing distress. In addition, men’s mental well-being was significantly better than that of women. Conclusion: Overall this research signified a need of General Practitioners to realize and understand that Common Mental Disorders are common in individuals presenting in primary health care set ups which would enable timely identification of vulnerable individuals so that interventions could be implemented accordingly.